"Essential non‐essentials": COVID‐19 policy missteps in Nigeria rooted in persistent myths about African food supply chains. Issue 1 (28th December 2020) - Liverpool‐Tasie, Lenis Saweda O.; Reardon, Thomas; Belton, Ben
Abstract: Food supply chains are extremely important for food access and livelihoods across Africa, but their role is often overlooked and underappreciated. Under normal conditions, the gap between myth and reality can result in the design of policies and programs with limited or negative impacts on food security and welfare. The shock of COVID‐19 has heightened this disconnect, with potentially dire consequences for food security. This paper demonstrates the importance of recognizing and accounting for the essential role of food supply chains when designing policy and interventions, particularly in response to COVID‐19, and provides recommendations for action based on current realities.